Genetic Variability of Galoba Durian (Amomum spp) Center Mollucas and North Halmahera Based on RAPD - Katerina Jagagura Peilouw; Adriana Hiariej; Anneke Pesik (Jurnal Penelitian Pendidikan IPA, 2022)
Galoba Durian is one of the endemic flora of Maluku, which is used as a medicinal plant and essential oil with red and green fruit colors. This study aimed to analyze the genetic variation of Galoba Durian in Central Maluku and North Halmahera based on the molecular marker of RAPD. This study began with a survey of sampling, isolation, and amplification of DNA using five RAPD primers. The results showed that all DNA bands were polymorphic as many as 67 with genetic similarity ranging from 20% - 31%, which grouped four samples into two groups. The first group is red Galoba Durian from North Halmahera (S1), red (S3) and green (S4) from Central Maluku, while the second group is green Galoba Durian from North Halmahera (S2).